Method for manufacturing a stretch film
Patent Information
- Application Number
- CN202410140878.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-17
- Filing Date
- 2024-02-01
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-02-01
AI Technical Summary
但是,若使用再循环材料来制膜树脂膜,则在制膜时产生非意图的交联物和/或低分子量物,结果是有时无法对拉伸膜赋予所期望的特性
[0015] According to embodiments of the present invention, even when using recycled materials to form the film resin membrane, the generation of crosslinks and/or low molecular weight substances can be suppressed, and a stretch film with desired properties can be manufactured.
Smart Images

Figure CN118514309B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for manufacturing stretch film. Background Technology
[0002] Stretch films, widely used in various industrial products, are manufactured by stretching resin films. For example, a method for manufacturing a stretch film has been proposed, in which the resin film is stretched in a direction intersecting the length direction while the two ends of the strip-shaped resin film are held by clamps in the width direction (see, for example, Patent Document 1).
[0003] In recent years, from the perspective of reducing environmental impact, there has been a desire to reuse waste generated during the manufacture of various industrial products. Therefore, research has been conducted on manufacturing stretched films by using recycled materials derived from resin product waste to form resin films and then stretching them. However, when using recycled materials to form resin films, unintended crosslinks and / or low molecular weight compounds are generated during film formation, sometimes resulting in the stretch film failing to acquire the desired properties.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent No. 7096940 Summary of the Invention
[0007] The problem that the invention aims to solve
[0008] The present invention was made to solve the above-mentioned prior art problems, and its main objective is to provide a method for manufacturing a stretch film that can suppress the generation of crosslinks and / or low molecular weight substances even when using recycled materials to form the film resin film, thereby enabling the manufacture of a stretch film with desired properties.
[0009] Methods for solving problems
[0010] [1] The method for manufacturing a stretch film according to an embodiment of the present invention includes the following steps: a step of preparing a virgin material comprising a first resin and a recycled material comprising a second resin and an incorporating component; a step of forming a strip-shaped resin film from the virgin material and the recycled material, wherein the recycled material forms both ends of the resin film in the width direction, and the virgin material forms a main body portion located between the two ends of the resin film in the width direction; a step of cutting the resin film to separate it into a first end film comprising the ends of the resin film in the width direction and a film-forming film comprising the main body portion; and a step of stretching the film-forming film in a direction intersecting the strip direction. The recycled material has a continuous phase composed of the second resin and a dispersed phase composed of the incorporating component. The maximum size of the dispersed phase is 500 nm or less.
[0011] [2] In the method for manufacturing the stretch film described in [1] above, the maximum size of the dispersed phase may be 10 nm or more and 200 nm or less.
[0012] [3] The method for manufacturing the stretch film described in [1] or [2] above may further include the step of cutting off both ends of the stretch film in the width direction to obtain a second end film.
[0013] [4] The method for manufacturing the stretch film described in any one of [1] to [3] above may further include a step of preparing a recycled material from a recycled resin material comprising the first end film and / or the second end film described above.
[0014] Invention Effects
[0015] According to embodiments of the present invention, even when using recycled materials to form the film resin membrane, the generation of crosslinks and / or low molecular weight substances can be suppressed, and a stretch film with desired properties can be manufactured. Attached Figure Description
[0016] Figure 1 This is a schematic top view of the resin film involved in the method for manufacturing a stretch film according to one embodiment of the present invention.
[0017] Figure 2 It will be by Figure 1 A schematic top view of a stretched film obtained by stretching a resin film.
[0018] Explanation of symbols
[0019] 3. Resin film
[0020] 31. End of the resin film in the width direction
[0021] 32 Main Body
[0022] 4. Membrane Formation
[0023] 5. Stretch film
[0024] 6. End membrane at the first end
[0025] 7. Second end membrane Detailed Implementation
[0026] The following describes embodiments of the present invention, but the present invention is not limited to these embodiments. Furthermore, to make the description clearer, the accompanying drawings sometimes schematically represent the width, thickness, shape, etc., of various parts compared to the embodiments, but these are merely examples and do not limit the interpretation of the present invention.
[0027] (Definitions of terms and symbols)
[0028] The definitions of terms and symbols used in this specification are as follows.
[0029] (1) Refractive index (nx, ny, nz)
[0030] “nx” is the refractive index in the direction where the refractive index is maximum (i.e., the slow axis direction), “ny” is the refractive index in the direction orthogonal to the slow axis (i.e., the fast axis direction), and “nz” is the refractive index in the thickness direction.
[0031] (2) In-plane phase difference (Re)
[0032] “Re(λ)” is the in-plane phase difference measured at 23°C using light with a wavelength of λ nm. For example, “Re(550)” is the in-plane phase difference measured at 23°C using light with a wavelength of 550 nm. When the thickness of the layer (film) is set to d (nm), Re(λ) is obtained using the formula: Re(λ)=(nx-ny)×d.
[0033] (3) Angle
[0034] Unless otherwise specified, when referring to angles in this instruction manual, the angles include both clockwise and counterclockwise angles.
[0035] A. An overview of the manufacturing method of stretch film
[0036] Figure 1 This is a schematic top view of the resin film involved in the method for manufacturing a stretch film according to one embodiment of the present invention; Figure 2 It will be by Figure 1 A schematic top view of a stretched film obtained by stretching a resin film.
[0037] The method for manufacturing a stretch film according to an embodiment of the present invention includes, in sequence, a preparation step, a film forming step, a first cutting step, and a stretching step.
[0038] In the preparation process, virgin material and recycled material are prepared. The virgin material comprises a first resin. The recycled material comprises a second resin and incorporating components. The recycled material has a continuous phase composed of the second resin and a dispersed phase composed of the incorporating components. The maximum size of the dispersed phase is 500 nm or less, preferably 350 nm or less, more preferably 250 nm or less, further preferably 200 nm or less, and particularly preferably 100 nm or less. It should be noted that the maximum size of the dispersed phase can be determined, for example, by cross-sectional observation using a scanning electron microscope.
[0039] In the film-making process, a long strip of resin film 3 (refer to) is made from virgin materials and recycled materials. Figure 1More specifically, the two ends 31 of the resin film 3 in the width direction are formed from recycled material, and the main body portion 32 located between the two ends 31 in the width direction of the resin film 3 is formed from virgin material. In the resin film 3, the main body portion 32 is integrally continuous with the two ends 31 in the width direction. In the first cutting process, the resin film 3 is cut to separate it into a first end film 6 containing the ends 31 in the width direction of the resin film 3 and a film-forming film 4 containing the main body portion. In the stretching process, the film-forming film 4 is stretched in a direction intersecting the strip direction (see reference). Figure 2 ).
[0040] The inventors have studied the production of stretched films (especially optical films) by using recycled materials and virgin materials to form resin films and stretching these resin films. They discovered that during the formation of resin films from recycled and virgin materials, the viscosity difference between the molten recycled and virgin materials sometimes causes stagnation due to variations in the flowability of the molten material within the film-forming apparatus (typically piping), resulting in unintended crosslinks and / or low molecular weight compounds. In such cases, the properties of the resulting stretched film may become uneven due to the presence of crosslinks and / or low molecular weight compounds. Therefore, in-depth research was conducted on recycled materials, and it was found that adjusting the size of the dispersed phase contained in the recycled material can suppress the generation of crosslinks and / or low molecular weight compounds during film formation. Specifically, firstly, recycled materials with a maximum dispersed phase size below the aforementioned upper limit are prepared. Additionally, virgin materials are prepared separately. Next, one resin film 3 is formed, with the recycled material forming both ends 31 in the width direction and the virgin material forming the main body 32 of the resin film 3. At this point, since the maximum size of the dispersed phase contained in the recycled material is below the aforementioned upper limit, the flowability of the molten recycled material and the virgin material can be appropriately adjusted, and the generation of crosslinks and / or low molecular weight substances can be suppressed. Therefore, even when using recycled materials to form the film resin membrane 3, a stretched membrane 5 with the desired properties can be stably manufactured.
[0041] In one embodiment, the maximum size of the dispersed phase is, for example, 1 nm or more, preferably 10 nm or more, more preferably 30 nm or more, and even more preferably 50 nm or more. If the maximum size of the dispersed phase is at or above the aforementioned lower limit, recycled materials can be successfully manufactured.
[0042] The following is a detailed explanation of each step in the manufacturing process of the stretch film.
[0043] B. Preparation process
[0044] In the preparation process, virgin materials and recycled materials are prepared separately as described above.
[0045] B-1. Raw Materials
[0046] The virgin material is a synthetic resin material that does not contain recycled resin. Examples of the virgin material's form include granules and powder. In one embodiment, the virgin material is prepared as virgin granules. The case where the virgin material is virgin granules will be described in detail below.
[0047] Virgin pellets can have any suitable shape and size. Typically, virgin pellets are cylindrical. The average maximum length of virgin pellets is, for example, 1.0 mm or more and 5.0 mm or less. The mass of each virgin pellet is, for example, 5 mg or more and 25 mg or less.
[0048] The virgin pellets (virgin material) contain a first resin and substantially no other components. The content of the first resin in the virgin pellets is, for example, 99.0% by mass or more, preferably 99.2% by mass or more, more preferably 99.5% by mass or more, and representatively, 100% by mass or less. That is, the content of other components in the virgin pellets is, for example, 1.0% by mass or less, preferably 0.8% by mass or less, more preferably 0.5% by mass or less, further preferably 0.2% by mass or less, particularly preferably 0.09% by mass or less, especially preferably 0.05% by mass or less, and representatively, 0% by mass or more.
[0049] The first resin is selected arbitrarily and appropriately according to the intended use of the stretch film.
[0050] Examples of primary resins include, for example, polycarbonate resins, polyvinyl acetal resins, cycloolefin resins, (meth)acrylic resins, cellulose ester resins, cellulose resins, polyester resins, polyester carbonate resins, olefin resins, and polyurethane resins. It should be noted that (meth)acrylic resins refer to acrylic resins and / or methacrylic resins. These primary resins can be used alone or in combination.
[0051] The first resin contained in the virgin granules preferably includes polycarbonate (PC) resins, cyclic olefin (COP) resins, (meth)acrylic resins, and polyester resins (typically polyethylene terephthalate (PET)), and more preferably PC resins. If the first resin is such a resin material, the stretch film (especially optical film) can be stably endowed with the desired properties.
[0052] Examples of PC-based resins include those containing structural units derived from dihydroxy compounds. Specific examples of dihydroxy compounds include 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 9,9-bis(4-hydroxy-3-ethylphenyl)fluorene, 9,9-bis(4-hydroxy-3-n-propylphenyl)fluorene, 9,9-bis(4-hydroxy-3-isopropylphenyl)fluorene, 9,9-bis(4-hydroxy-3-n-butylphenyl)fluorene, 9,9-bis(4-hydroxy-3-sec-butylphenyl)fluorene, 9,9-bis(4-hydroxy-3-tert-butylphenyl)fluorene, 9,9-bis(4-hydroxy-3-cyclohexylphenyl)fluorene, 9,9-bis(4-hydroxy-3-phenylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene, and 9,9-bis(4-( 2-Hydroxyethoxy)-3-methylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-isopropylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-isobutylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-tert-butylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-cyclohexylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-phenylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3,5-dimethylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-tert-butyl-6-methylphenyl)fluorene, 9,9-bis(4-(3-hydroxy-2,2-dimethylpropoxy)phenyl)fluorene. In addition to structural units derived from the aforementioned dihydroxy compounds, PC resins may also contain structural units derived from dihydroxy compounds such as isosorbide, isomannitol, isoidulitol, spirodiol, dioxanediol, diethylene glycol (DEG), triethylene glycol (TEG), polyethylene glycol (PEG), cyclohexanediethanol (CHDM), tricyclodecanediethanol (TCDDM), and bisphenols.
[0053] Details of the aforementioned PC-based resins are described, for example, in Japanese Patent Application Publication No. 2012-67300 and Japanese Patent No. 3325560. The descriptions in these patent documents are incorporated herein by reference.
[0054] The melt viscosity A of the virgin granules (virgin material) can be varied depending on the type of the first resin. The melt viscosity A of the virgin granules is, for example, 300 Pa·s or more, preferably 500 Pa·s or more, more preferably 1000 Pa·s or more, for example, 3000 Pa·s or less, preferably 2500 Pa·s or less. It should be noted that the melt viscosity of the granules can be determined, for example, by following the method in JIS K 7199.
[0055] Virgin pellets can be prepared by any suitable method. The preparation method of virgin pellets can be wire cutting or thermal cutting. Details of the preparation method of virgin pellets are described, for example, in Japanese Patent Application Publication No. 2013-181105. The description in that patent document is incorporated herein by reference.
[0056] B-2. Recycled Materials
[0057] Details of the recycled material will be described later, but it is a recycled resin material. Examples of the form of the recycled material include granules and powders. In one embodiment, the recycled material is prepared as recycled granules. The case where the recycled material is recycled granules will be described in detail below.
[0058] The shape and size of the recycled granules can be described in the same manner as those of the virgin granules described above. The recycled granules comprise the second resin described above and admixtures incorporated into the second resin. In the recycled granules, the second resin forms the continuous phase as the matrix resin, and the admixtures form the dispersed phase dispersed in the continuous phase in a particulate form. The second resin contained in the recycled granules (recycled material) is representatively the same as the first resin contained in the virgin granules (virgin material).
[0059] The content of the second resin in the recycled granules is, for example, 40.0% by mass or more, preferably 50.0% by mass or more, more preferably 70.0% by mass or more, and even more preferably 90.0% by mass or more, for example, 99.1% by mass or less.
[0060] The proportion of the mixed components in the recycled pellets is, for example, 60.0% by mass or less, preferably 50.0% by mass or less, more preferably 30.0% by mass or less, and even more preferably 10.0% by mass or less. The lower limit of the proportion of the mixed components in the recycled pellets is, for example, 0.3% by mass, and also, for example, 0.5% by mass, and also, for example, 0.9% by mass.
[0061] In the recycled granules, the mass ratio of the mixed component to the second resin (mixed component / second resin) is, for example, 0.01 or more, for example, 1.5 or less, preferably 1.0 or less. If the mixed component / second resin is within the above range, the non-uniformity in the resin film can be stably reduced.
[0062] The components contained in recycled pellets (recycled materials) typically include foreign matter. In addition to foreign matter, the components may also include resin components different from the second resin. Foreign matter is a solid component different from the resin component. Examples of foreign matter include amide-based foreign matter and fibrous foreign matter. Foreign matter may be incorporated into the recycled pellets alone or in combination.
[0063] The proportion of foreign matter mixed into the component is, for example, more than 1% by volume and less than 100% by volume, or more than 10% by volume and less than 50% by volume.
[0064] The largest foreign object in the mixed component has a maximum size of, for example, less than 3 mm, preferably less than 1 mm. If the maximum size of the largest foreign object is less than the above-mentioned upper limit, unevenness in the resin film can be stably suppressed. It should be noted that the maximum size of the foreign object can be determined, for example, by a particle counter.
[0065] In one embodiment, the foreign body comprises a first foreign body with a maximum size of 500 μm or more but less than 1 mm and a second foreign body with a maximum size of less than 500 μm. The foreign body may also comprise a third foreign body with a maximum size of more than 1 mm.
[0066] The proportion of the first foreign substance in the mixed component is, for example, 5% or more by volume, for example, 50% or less by volume, preferably 40% or less by volume.
[0067] The proportion of the second foreign substance in the mixed components is, for example, 50% by volume or more, preferably 60% by volume or more, and for example, 95% by volume or less.
[0068] If the proportions of the first and / or second foreign matter are within the above range, unevenness in the resin film can be more stably suppressed.
[0069] In addition to foreign matter, the mixed component may also contain a resin component different from the second resin. Examples of resin components include those identical to the first resin described above. The mixed component may contain one or more resin components. In one embodiment, the resin component comprises an olefin-based resin (typically polyethylene).
[0070] The proportion of resin component mixed into the composition is, for example, 0% or more and 99% or less by volume, or, for example, 50% or more and 90% or less by volume.
[0071] The bubble rate of the recycled granules is, for example, 10% by volume or less, preferably 3% by volume or less, and more preferably 0% by volume. It should be noted that the bubble rate can be determined by observation and analysis using a microscope. If the bubble rate of the recycled granules is below the above-mentioned upper limit, the incorporation of bubbles into the resin film can be suppressed.
[0072] The melt viscosity C of the recycled granules (recycled material) can be appropriately varied depending on the type of the second resin and the mixed components. The melt viscosity C of the recycled granules is, for example, 200 Pa·s or more, preferably 350 Pa·s or more, for example, 2800 Pa·s or less, preferably 2300 Pa·s or less.
[0073] The melt viscosity of the virgin pellets (virgin material) and the melt viscosity of the recycled pellets (recycled material) satisfy, for example, the following equation (1), and preferably the following equation (2).
[0074] [Mathematical Expression 1]
[0075]
[0076] [Mathematical Expression 2]
[0077]
[0078] (In equations (1) and (2), A represents the melt viscosity of the virgin material [Pa·s], and C represents the melt viscosity of the recycled material [Pa·s].)
[0079] The melt viscosity A of the virgin granules and the melt viscosity C of the recycled granules satisfy the above formula (1). The absolute value of the difference in melt viscosity between the virgin granules and the recycled granules relative to the melt viscosity A of the virgin granules (|(CA) / A|) is 0 or more, preferably 0.05 or more, more preferably 0.08 or more, less than 0.65, preferably less than 0.60, more preferably less than 0.55, further preferably less than 0.45, particularly preferably less than 0.35, especially preferably less than 0.23, and most preferably less than 0.20. If |(CA) / A| is within the above range, the flowability of the molten recycled material and the virgin material can be adjusted more appropriately, and the generation of crosslinks and / or low molecular weight substances in the resin film can be further suppressed.
[0080] B-2-1. Preparation method of recycled pellets
[0081] Recycled pellets can be prepared from recycled resin materials using any suitable method.
[0082] Recycled resin materials can be obtained by recycling waste resin products or waste generated during the manufacture of resin products. Examples of resin products include optical films such as retardation films; packaging materials made of thermoplastic resins such as polyethylene terephthalate (PET) and nylon. Among these resin products, optical films are preferred, and retardation films are more preferred. That is, recycled granules are preferably prepared from optical films (typically retardation films) and / or waste generated during the manufacture of optical films. Details will be described later, but in the method for manufacturing stretch films according to embodiments of the present invention, end films (first end films and / or second end films) generated as byproducts can be suitably used as recycled resin materials in the preparation of recycled granules. It should be noted that recycled resin materials can also be recycled multiple times. That is, recycled granules can also be prepared from resin products (typically optical films) manufactured with recycled resin materials and / or waste generated during the manufacture of such resin products.
[0083] As a method for preparing recycled pellets, examples include methods similar to those for preparing virgin pellets described above. In one embodiment, the method for preparing recycled pellets includes: a step of melting recycled resin material (melting step); and a step of extruding the molten recycled resin material (extrusion step).
[0084] The moisture content of the recycled resin material supplied to the melting process is, for example, 2.0% by mass or less, preferably less than 1.0% by mass, more preferably less than 0.9% by mass, and even more preferably less than 0.8% by mass. If the moisture content of the recycled resin material is below the aforementioned upper limit, the generation of bubbles in the resin film prepared using recycled granules can be suppressed. The lower limit of the moisture content in the recycled resin material is typically 0.01% by mass or more. It should be noted that the moisture content of the recycled resin material can be determined, for example, by the Karl Fischer method.
[0085] To adjust the moisture content of the recycled resin material to the aforementioned range, any suitable method can be employed. For example, one method for adjusting the moisture content of the recycled resin material is to store it in a moisture-proof bag.
[0086] Moisture-proof bags can have any suitable composition. For example, a packaging material with aluminum fused to the inner bag can be cited as an example of a moisture-proof bag. The moisture permeability of the moisture-proof bag is, for example, 10 g / m³. 2 • Less than 24 hours, preferably 5g / m 2 • Less than 24 hours, preferably 3g / m 2 • Less than 24 hours. Water permeability can be measured, for example, using the cup method.
[0087] The storage time is, for example, 2 hours or more, preferably 12 hours or more, for example, 72 hours or less, preferably 36 hours or less. If such a method is used, even if the recycled resin material is stored for the above-mentioned time, the moisture content of the recycled resin material can be stably maintained within the above-mentioned range.
[0088] The storage temperature is, for example, above 0°C and below 30°C, and the storage humidity is, for example, above 0%RH (relative humidity) and below 60%RH (relative humidity).
[0089] In the melting process, the recycled resin material is heated and melted. Typically, the recycled resin material is fed into a drum containing a screw, heated and melted, and then mixed by the screw.
[0090] The heating temperature and heating time can be set arbitrarily and appropriately according to the type of recycled resin material. The heating temperature is, for example, above 80°C and below 150°C. The heating time (retention time) is, for example, above 6 hours and below 48 hours.
[0091] The screw rotation speed is, for example, 5 rpm or more, preferably 10 rpm or more, more preferably 20 rpm or more, and even more preferably 40 rpm or more, for example, 200 rpm or less, preferably 100 rpm or less, and more preferably 80 rpm or less. If the screw rotation speed is above the aforementioned lower limit, the maximum size of the dispersed phase in the recycled pellets can be stably adjusted to below the aforementioned upper limit. If the screw rotation speed is above the aforementioned lower limit, the incorporation of air bubbles into the recycled pellets can be suppressed.
[0092] The length L of the screw is 15 or more, preferably 20 or more, for example, 60 or less, and preferably 40 or less, relative to the diameter D of the screw.
[0093] Thus, a molten recycled resin material (hereinafter referred to as molten resin) is obtained.
[0094] In one embodiment, the molten resin is passed through a filter before being fed into the extrusion molding process. This removes large foreign matter contained in the molten resin.
[0095] The filter can take any suitable configuration. Examples of filters include screens and disc filters, with screens being the preferred choice.
[0096] The mesh size of the screen is, for example, 2.6 mm or less (8 mesh), preferably 2.0 mm or less (10 mesh), more preferably 0.60 mm or less (30 mesh), and even more preferably 0.15 mm or less (100 mesh), for example, 0.034 mm or more (400 mesh), preferably 0.045 mm or more (300 mesh), and more preferably 0.060 mm or more (250 mesh). If the mesh size is below the upper limit mentioned above, coarse foreign objects can be smoothly removed from the molten resin, especially if the mesh size is less than 1.0 mm, coarse foreign objects with a maximum size exceeding 1 mm can be removed from the molten resin. If the mesh size is above the lower limit mentioned above, the molten resin can pass through smoothly.
[0097] In the extrusion molding process, molten resin is ejected from the die and then cooled to solidify. This produces recycled granules.
[0098] In the case where the recycled granules are prepared by wire cutting, molten resin is ejected from a mold in the form of filaments and then cooled to obtain filaments composed of recycled resin material. These filaments are then cut to specified dimensions to obtain the recycled granules.
[0099] When the preparation method of recycled granules is thermal cutting, the molten resin is sprayed out of the mold in the form of filaments and then immediately cut to obtain recycled granules.
[0100] C. Film-making process
[0101] like Figure 1 As shown, in the film-making process, a long strip of resin film 3 is made from the aforementioned virgin granules and recycled granules. More specifically, the two ends 31 in the width direction of the resin film 3 are formed from recycled granules, and the main body 32 of the resin film 3 is formed from virgin granules, thus making one resin film 3.
[0102] Detailed descriptions of the resin film preparation method are provided, for example, in Japanese Patent Application Publication No. 2006-315275. The description in that patent document is incorporated herein by reference. More specifically, in the method for manufacturing a brittle resin film described in Japanese Patent Application Publication No. 2006-315275, a resin film 3 can be prepared by using virgin granules as the brittle resin A and recycled granules as the tough resin B.
[0103] At this point, if the maximum size of the dispersed phase contained in the recycled pellets is below the above-mentioned upper limit, the flowability of the molten recycled material and the virgin material can be appropriately adjusted, and the generation of crosslinks and / or low molecular weight substances can be suppressed.
[0104] It should be noted that, as a cross-linking agent, representative examples include gel-like foreign matter produced by the thermal cross-linking of resin.
[0105] In addition, examples of low molecular weight substances include substances whose molecular weight is reduced by the thermal degradation of resins, and sublimations of additives such as antioxidants.
[0106] The resin film 3 obtained in the film-forming process can have any suitable configuration. The resin film 3 is elongated as described above. The dimensions of the resin film 3 in each direction can be any suitable value. The width of the resin film 3 (the dimension in the direction orthogonal to the elongated direction) is, for example, 500 mm or more, preferably 700 mm or more, for example, 2500 mm or less, preferably 2000 mm or less. The thickness of the resin film 3 is, for example, 40 μm or more, preferably 60 μm or more, for example, 200 μm or less, preferably 180 μm or less.
[0107] D. First cutting process
[0108] In the first cutting process, the two ends 31 of the resin film 3 in the width direction are cut off respectively.
[0109] In the example shown, two cutting lines 33 are formed in the resin film 3. The cutting lines 33 extend along the elongated direction of the resin film 3. The two cutting lines 33 are formed with a predetermined interval between them in the width direction of the resin film 3, and the two cutting lines 33 are also formed with a predetermined interval between them and the edge of the resin film 3 in the width direction.
[0110] Thus, the resin membrane 3 is separated into two first end membranes 6 containing the ends 31 in the width direction of the resin membrane 3 and a film-forming membrane 4 containing the main body portion 32. The two first end membranes 6 and the film-forming membrane 4 are each elongated strips.
[0111] When the width of the resin film 3 is set to 100%, the width of the first end film 6 is, for example, 1% or more, preferably 5% or more, more preferably 10% or more, for example, 50% or less, preferably 30% or less. The width of the first end film 6 is, for example, 10 mm or more, preferably 50 mm or more, more preferably 100 mm or more, for example, 1000 mm or less, preferably 600 mm or less. If the width of the first end film is above the aforementioned lower limit, the first end film can sufficiently contain the portion from the recycled granule source. If the width of the end film is below the aforementioned upper limit, the yield of the stretched film can be improved.
[0112] The first end membrane 6 can also be recycled by any suitable method. The recycled first end membrane 6 can be suitably used as a recycled resin material in the above-described method for preparing recycled granules.
[0113] E. Stretching process
[0114] like Figure 2As shown, in the stretching process, the elongated film 4 is stretched in a direction intersecting the length of the strip. Any suitable stretching method can be used. Various stretching methods, such as free-end stretching and fixed-end stretching, can be used individually, simultaneously, or sequentially. Fixed-end uniaxial stretching is a preferred stretching method.
[0115] Fixed-end uniaxial stretching is typically performed using a stretching device equipped with clamps that hold the width-direction end of the film 4. A typical stretching device is a tenter frame stretching device. With the width-direction ends of the film 4 held (typically clamped) by the clamps, the stretching device stretches the film 4 in a direction intersecting the elongation direction. The stretching direction can be substantially orthogonal to the elongation direction of the film 4 (e.g., 90° ± 1° relative to the elongation direction), or it can be a direction intersecting both the elongation and width directions of the film 4.
[0116] Details of the stretching process are described, for example, in Japanese Patent No. 7096940, Japanese Unexamined Patent Publication No. 2004-226686, and International Publication No. 2007 / 111313. The descriptions in these patent documents are incorporated herein by reference.
[0117] Therefore, as Figure 2 As shown, a long strip of stretched film 5 is manufactured. The stretching ratio in the width direction during the stretching process (width of the stretched film / width of the film-forming film) is, for example, 1.1 or more, preferably 1.5 or more, for example, 6.0 or less, preferably 4.0 or less.
[0118] The stretched film 5, typically, has a slow axis in the stretching direction described above, and is constructed as a phase retardation film. The refractive index of the stretched film 5 shows a relationship of nx > ny.
[0119] In one embodiment, the stretch film 5 functions as a λ / 4 plate. When the product film functions as a λ / 4 plate, the in-plane phase difference Re(550) of the stretch film 5 is, for example, 100 nm to 180 nm, preferably 135 nm to 155 nm.
[0120] In another embodiment, the stretching membrane 5 functions as a λ / 2 plate. When the stretching membrane functions as a λ / 2 plate, the in-plane phase difference Re(550) of the stretching membrane is, for example, 230 nm to 310 nm, preferably 250 nm to 290 nm.
[0121] There are no particular limitations on the wavelength dependence of the stretched film 5. The stretched film 5 preferably exhibits an anti-dispersion wavelength dependence. The Re(450) / Re(550) ratio of the stretched film 5 is preferably 0.8 or higher and lower than 1.0, more preferably 0.8 to 0.95. Furthermore, the Re(550) / Re(650) ratio of the stretched film 5 is preferably 0.8 or higher and lower than 1.0, more preferably 0.8 to 0.97.
[0122] The absolute value of the photoelastic coefficient of the stretched film 5 is, for example, 2 × 10⁻⁶. -12 (m 2 / N)~100×10 -12 (m 2 / N), preferably 5×10 -12 (m 2 / N)~50×10 -12 (m 2 / N).
[0123] F. Second cutting process
[0124] In one embodiment, the manufacturing of the stretch film further includes a second cutting step. In the second cutting step, both ends of the stretch film 5 in the width direction are cut off respectively.
[0125] In the example shown, two cutting lines 55 are formed in the stretch film 5. The cutting lines 55 extend along the longitudinal direction of the stretch film 5. The two cutting lines 55 are formed with a predetermined interval between them in the width direction of the stretch film 5, and the two cutting lines 55 are also formed with a predetermined interval between them and the end edge of the stretch film 5 in the width direction.
[0126] If uniaxial stretching at a fixed end is performed during the stretching process, clamping marks 51 may sometimes be formed at both ends of the stretch film 5 in the width direction. The clamping marks 51 are harder and more brittle than the parts of the stretch film 5 other than the clamping marks 3.
[0127] Furthermore, the slow axis of the stretch membrane 5 sometimes deviates in the width direction. More specifically, the direction of the slow axis of the stretch membrane 5 tends to deviate from the desired angle at its width-direction ends. This axial deviation is substantially not apparent at the center of the stretch membrane 5 in the width direction, but becomes larger closer to the width-direction ends. In the stretch membrane 5 of the illustrated example, at the center of the width direction, the slow axis is substantially parallel to the aforementioned stretching direction (e.g., axial deviation less than 0° ± 1°). Furthermore, at the width-direction ends of the stretch membrane 5, the slow axis may also intersect the aforementioned stretching direction (e.g., axial deviation of 1° to 3°).
[0128] Therefore, if the second cutting process is performed, the clamping marks 51 of the clamp and / or the portion of the stretch film with relatively large axial deviation can be removed from the stretch film 5. Furthermore, two second end films 7 corresponding to the two ends in the width direction of the stretch film 5 are obtained from the stretch film 5.
[0129] The second end film 7 in the example includes clamping traces 51. Furthermore, the two second end films 7 are cut to form a stretch film 2, which is then used as a product film 8. That is, in the second cutting process, the stretch film 5 is typically separated into two second end films 7 and a product film 8. The product film 8 is typically used as the aforementioned phase difference film.
[0130] When the width of the stretch film 5 is set to 100%, the width of the second end film 7 is, for example, 0.5% or more, preferably 1.0% or more, more preferably 5.0% or more, even more preferably 10.0% or more, for example, 30% or less, preferably 25% or less, even more preferably 20% or less. The width of the second end film 7 is, for example, 10 mm or more, preferably 20 mm or more, even more preferably 100 mm or more, even more preferably 200 mm or more, for example, 600 mm or less, preferably 500 mm or less, even more preferably 300 mm or less.
[0131] If the width of the second end film is above or above the aforementioned lower limit, the second end film can stably contain the entire clamping traces, and the second end film can contain the portion of the stretch film with a relatively large axial deviation. As a result, the retention of clamping traces in the product film can be suppressed, and the axial deviation in the product film can be reduced. If the width of the second end film is below or above the aforementioned upper limit, the yield of the product film can be improved.
[0132] The second end membrane 7 can also be recycled by any suitable method. The recycled second end membrane 7 can be suitably used as a recycled resin material in the above-described method for preparing recycled granules. In other words, the manufacture of the stretch film can further include a step of preparing recycled granules from a recycled resin material containing the first end membrane 6 and / or the second end membrane 7.
[0133] Example
[0134] The present invention will now be specifically described through examples, but the present invention is not limited to these examples. The methods for measuring each characteristic are described below. It should be noted that, unless otherwise specified, "parts" and "%" in the examples and comparative examples refer to mass. Furthermore, the methods for measuring each characteristic in the examples and comparative examples are described below.
[0135] (1) Determination of melt viscosity of virgin and recycled pellets
[0136] By following the method of JIS K 7199, at a shearing rate of 100 sec -1 The melt viscosity of the virgin and recycled pellets used in the examples and comparative examples was determined under a measurement temperature of 24°C. The results are shown in Tables 1 to 3.
[0137] (2) Determination of the maximum size of the dispersed phase in recycled pellets
[0138] The maximum size of the dispersed phase in the recycled pellets used in the examples and comparative examples was determined by observation using a scanning microscope. The results are shown in Tables 1-3.
[0139] (3) Determination of the maximum size of foreign matter contained in recycled aggregates and determination of the content ratio of each component in the foreign matter.
[0140] The maximum size of foreign matter in the recycled pellets used in the Examples and Comparative Examples was determined using a particle counter. The foreign matter included a first foreign matter with a maximum size x of 500 μm or more but less than 1 mm, and / or a second foreign matter with a maximum size x of less than 500 μm. Furthermore, in Example 13, in addition to the first and second foreign matter, a third foreign matter with a maximum size x of 1 mm or more was also included. The proportions (volume %) of the first, second, and third foreign matter were calculated using observation and analysis with an optical microscope. The results are shown in Tables 1-3.
[0141] (4) Moisture content in the end membrane
[0142] In the examples and comparative examples, the moisture content of the end-film (recycled resin material) to be supplied to the manufacturing process of recycled granules was determined by the Karl Fischer method. The results are shown in Tables 1 to 3.
[0143] (5) Content of cross-linked compounds and low molecular weight compounds
[0144] Regarding the content of crosslinkers and / or low molecular weight compounds in the resin films prepared in the examples and comparative examples, the crosslinker content is determined by utilizing AOI per m 2 The number of molecules was counted, and the degree of whitening of low molecular weight compounds was determined by visual observation of the membrane appearance, and evaluated according to the following criteria. The results are shown in Tables 1-3.
[0145] 5: Crosslinking / membrane whitening is not visible to the naked eye.
[0146] 4: Crosslinking material is slightly visible at 5 particles / m 2 The following is an example of membrane whitening.
[0147] 3: More than 5 cross-links are visible per m 2 And 10 per m 2 The following is an example of membrane whitening.
[0148] 2: More than 10 cross-links are clearly visible per m. 2 And 50 per m 2 The following is an example of membrane whitening.
[0149] 1: More than 50 cross-links / m are clearly visible. 2 And 100 per m 2 The following is an example of membrane whitening.
[0150] <<Preparation of End-Membranes>>
[0151] <Preparation Examples 1-6>
[0152] Following the same procedure as in Manufacturing Example 9 of Japanese Patent Application Publication No. 2022-150732, a resin film made of PC-based resin was prepared, and the resin film was stretched to prepare a stretched film made of PC-based resin. The thickness of the stretched film was 48 μm.
[0153] Next, the two ends of the stretch film in the width direction are cut using a strip cutter (cutting device) to obtain two end films (recycle count: 1). The width of each of the two end films is 250mm.
[0154] Next, the obtained end membrane was washed with water. Then, the end membrane was dried at 100°C for 10 minutes (washing count: 1).
[0155] Next, place the end film into a moisture-proof bag (trade name: moisture-proof bundled bag, single-seam moisture-proof type, manufactured by Yamaguchi Packaging Industrial Co., Ltd.) under the conditions shown in Table 1 or 3, and store for 24 hours.
[0156] <Preparation Example 7>
[0157] Except for changing the moisture-proof bag to a non-moisture-proof bag (trade name: inner bag aluminum bag, manufactured by Yamaguchi Packaging Industrial Co., Ltd.), the same procedure as in Preparation Example 1 was followed to prepare the end film and store it.
[0158] <Preparation Examples 8-13>
[0159] Using the end-film obtained in Preparation Example 1, recycled granules were manufactured using the same method as in Example 1 described later (preparation step). A resin film was then formed from the virgin granules and recycled granules (film forming step). The resin film was cut to separate a first end-film and a film forming membrane (first cutting step). Next, the film forming membrane was stretched (stretching step), and the resulting stretched membrane was cut to separate a second end-film and a finished product film (second cutting step). Then, using the obtained second end-film, the preparation step, film forming step, first cutting step, stretching step, and second cutting step were repeatedly performed until the number of recycling cycles shown in Table 1 or 3 was reached. Thus, an end-film (second end-film) with the number of recycling cycles shown in Table 1 or 3 was prepared. The obtained end-film was then stored in the same manner as in Preparation Example 1.
[0160] <Preparation Examples 14-16>
[0161] Following the same procedure as in Manufacturing Example 9 of Japanese Patent Application Publication No. 2022-150732, a resin film made of PC-based resin was prepared, and the resin film was stretched to prepare a stretched film made of PC-based resin. The thickness of the stretched film was 48 μm.
[0162] Next, a polyethylene (PE) film (thickness: 48 μm) is attached to the surface of the stretch film as a protective film through an acrylic adhesive layer. Then, the two ends of the laminated stretch film and protective film in the width direction are cut using a strip cutter (cutting device) to obtain two end films (recycle count: 1). Each of the two end films has a width of 250 mm.
[0163] Next, the obtained end-film was washed with water. Then, the end-film was dried at 100°C for 10 minutes (washing count: 1). Afterward, the end-film was stored in the same manner as in Preparation Example 1.
[0164] <Preparation Example 17>
[0165] Except for changing the thickness of the PE film used as a protective film to 96 μm, the same procedure as in Preparation Example 14 was followed to prepare the end film and store it.
[0166] <Preparation Example 18>
[0167] Except for repeating the washing and drying of the end membrane five times, the same procedure as in Preparation Example 1 was followed to prepare and store the end membrane.
[0168] <Preparation Examples 19 and 20>
[0169] Except for changing the resin film made of PC-based resin to a resin film made of PET (manufactured by Toray Industries, part number "50U48"), the end films were prepared and stored in the same manner as in Preparation Example 1. It should be noted that the thickness of the stretched film obtained by stretching the resin film was 50 μm.
[0170] <Preparation Example 21>
[0171] Except that the end film obtained in Preparation Example 19 was used instead of the end film obtained in Preparation Example 1, the same procedure as in Preparation Example 8 was followed, repeatedly performing the preparation step, film-making step, first cutting step, stretching step, and second cutting step until the number of recycles shown in Table 2 was reached. Thus, an end film (second end film) with the number of recycles shown in Table 2 was prepared. The resulting end film was then stored in the same manner as in Preparation Example 1.
[0172] <Preparation Example 22>
[0173] Except for changing the resin film made of PC-based resin to a resin film made of PET (manufactured by Toray Industries, part number "50U48"), the same procedure as in Preparation Example 14 was followed to prepare and store the end film containing the PE film. It should be noted that the thickness of the stretched film obtained by stretching the resin film is 50 μm, and the thickness of the PE film is 50 μm.
[0174] <Preparation Examples 23 and 24>
[0175] Except for changing the resin film made of PC-based resin to a resin film made of acrylic resin (manufactured by KANEKA, product name "HTX-Z"), the preparation and storage of the end film were carried out in the same manner as in Preparation Example 1. It should be noted that the thickness of the stretched film obtained by stretching the resin film was 40 μm.
[0176] <Preparation Example 25>
[0177] Except that the end film obtained in Preparation Example 23 was used instead of the end film obtained in Preparation Example 1, the same procedure as in Preparation Example 8 was followed, repeatedly performing the preparation step, film-making step, first cutting step, stretching step, and second cutting step until the number of recycles shown in Table 2 was reached. Thus, an end film (second end film) with the number of recycles shown in Table 2 was prepared. The resulting end film was then stored in the same manner as in Preparation Example 1.
[0178] <Preparation Example 26>
[0179] Except for changing the resin film made of PC-based resin to a resin film made of acrylic resin (manufactured by KANEKA, product name "HTX-Z"), the same procedure as in Preparation Example 14 was followed to prepare and store the end film containing the PE film. It should be noted that the thickness of the stretched film obtained by stretching the resin film is 80 μm, and the thickness of the PE film used as the protective film is 80 μm.
[0180] <Preparation Examples 27 and 28>
[0181] Except for changing the resin film made of PC-based resin to a resin film made of COP-based resin (manufactured by ZEON Corporation, Japan, part number "ZF16"), the preparation and storage of the end film were carried out in the same manner as in Preparation Example 1. It should be noted that the thickness of the stretched film obtained by stretching the resin film is 40 μm.
[0182] <Preparation Example 29>
[0183] Except that the end film obtained in Preparation Example 27 was used instead of the end film obtained in Preparation Example 1, the same procedure as in Preparation Example 8 was followed, repeatedly performing the preparation step, film-making step, first cutting step, stretching step, and second cutting step until the number of recycles shown in Table 2 was reached. Thus, an end film (second end film) with the number of recycles shown in Table 2 was prepared. The resulting end film was then stored in the same manner as in Preparation Example 1.
[0184] <Preparation Example 30>
[0185] Except for changing the resin film made of PC-based resin to a resin film made of COP-based resin (manufactured by ZEON Corporation, Japan, part number "ZF16"), the same procedure as in Preparation Example 14 was followed to prepare and store the end film containing the PE film. It should be noted that the thickness of the stretched film obtained by stretching the resin film is 40 μm, and the thickness of the PE film serving as the protective film is also 40 μm.
[0186] [Examples 1-31, Comparative Examples 1 and 2]
[0187] The end-cap membranes obtained in each preparation example, after storage, were supplied as recycled resin material to a pellet manufacturing apparatus (wire cutting method) equipped with filters shown in Tables 1-3. In the pellet manufacturing apparatus, the end-cap membranes were heated to 270°C and melted, then passed through the filters shown in Tables 1-3. Subsequently, recycled pellets were manufactured by extrusion molding under the extrusion conditions (screw speed, compression ratio, and effective length) shown in Tables 1-3. The mass ratio of the mixed component / secondary resin in the recycled pellets is shown in Tables 1-3.
[0188] Furthermore, according to the method described in Japanese Patent Application Publication No. 2013-181105, virgin pellets are manufactured by melt extrusion. The virgin pellets contain the first resin shown in Tables 1-3. The content of the first resin in the virgin pellets is 100% by mass.
[0189] Next, a resin membrane is formed from virgin granules and recycled granules. More specifically, according to the embodiment disclosed in Japanese Patent Application Publication No. 2006-315275, the two ends of the resin membrane in the width direction are formed from recycled granules, and the main body portion located between the two ends of the resin membrane in the width direction is formed from virgin granules. The width of the resin membrane is 800 mm. The thickness of the resin membrane is 200 μm.
[0190] Next, the resin film is cut using a strip cutter (cutting device) to separate it into a first end film containing the end portion of the resin film in the width direction and a film forming film containing the main body portion. The width of each of the two first end films is 60 mm (7.5% when the width of the resin film is set to 100%).
[0191] Next, according to Manufacturing Example 9 of Japanese Patent Application Publication No. 2022-150732, the film was stretched along its width. This yielded a stretched film. The stretch ratio was 3.0 times. The width of the stretched film was 2000 mm.
[0192] Next, the stretch film is cut using a slitting machine (cutting device) to separate it into two second-end films and a finished product film. Each of the two second-end films has a width of 250 mm (12.5% when the width of the stretch film is set to 100%). The finished product film has a width of 1500 mm.
[0193] Table 1
[0194]
[0195] *Captures 50% of foreign objects within 100μm.
[0196] Table 2
[0197]
[0198] Table 3
[0199]
[0200] [evaluate]
[0201] As shown in Tables 1-3, it is known that in recycled granules, if the maximum size of the dispersed phase is less than 500 μm, the content of crosslinks and / or low molecular weight substances in the resin film can be reduced.
[0202] Industrial availability
[0203] The method for manufacturing the stretch film of the present invention can be used to manufacture stretch films available in various industrial products, and is particularly suitable for manufacturing optical films (specifically, phase retardation films).
Claims
1. A method for manufacturing a stretch film, comprising the following steps: The process of preparing virgin material containing first resin and recycled material containing second resin and mixed components; The process of forming a strip-shaped resin film from the virgin material and the recycled material, wherein, The process of forming the two ends of the resin film in the width direction from the recycled material, and forming the main body portion located between the two ends of the resin film in the width direction from the virgin material; The process of cutting the resin film to separate it into a first end film containing the end portion in the width direction of the resin film and a film forming film containing the main body portion; and The process of stretching the film along a direction intersecting the strip direction; The recycled material has a continuous phase composed of the second resin and a dispersed phase composed of the mixed components. The maximum size of the dispersed phase is below 500 nm.
2. The method for manufacturing a stretch film according to claim 1, wherein, The maximum size of the dispersed phase is greater than 10 nm and less than 200 nm.
3. The method for manufacturing a stretch film according to claim 1 or 2, wherein, The process further includes the step of cutting off both ends of the stretch film in the width direction to obtain a second end film.
4. The method for manufacturing a stretch film according to claim 3, wherein, The process further includes a step of preparing a recycled material from a recycled resin material comprising the first end membrane and / or the second end membrane.
Citation Information
Patent Citations
Rolled web for wideband quarter-wave plate, rolled web for wideband circularly polarizing plate, rolled web for optical device, and display device
JP2004226686A
Manufacturing method of brittle resin film and brittle resin film
JP2006315275A
Polycarbonate resin and transparent film comprising the same
JP2012067300A
Pellet mixture and method for producing resin molded article
JP2013181105A
Polarization plate with retardation layer and picture display unit using polarization plate with retardation layer
JP2022150732A